2022
DOI: 10.1111/irv.13043
|View full text |Cite
|
Sign up to set email alerts
|

Change in functional status associated with respiratory syncytial virus infection in hospitalized older adults

Abstract: Background Respiratory syncytial virus (RSV) causes severe respiratory illnesses in infants and older adults. Older adults are frequently hospitalized with RSV illness and may experience loss of function. This study evaluated longitudinal changes in function associated with RSV hospitalization in older adults. Methods Adults ≥60 years hospitalized with laboratory‐confirmed RSV were enrolled (N = 302). Demographics and comorbidities were collected. Functional status was assessed 2 weeks pre‐hospitalization by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 26 publications
(72 reference statements)
0
24
2
Order By: Relevance
“…7 Beyond hospitalization, complications from RSV can persist, with 23% of older adults requiring a higher level of care after discharge. 35 This is in comparison to research from California that has found a lower 1-year survival rate after admission for RSV than for influenza (74.2% versus 81.2%, p < 0.001). 36 Each year, 7 in 10 Canadian older adults choose to be vaccinated against influenza, 37 an indication that the majority view the consequences of influenza to be a greater risk than the potential for any adverse events associated with vaccination.…”
Section: Complacency and Rsv Vaccinationcontrasting
confidence: 46%
“…7 Beyond hospitalization, complications from RSV can persist, with 23% of older adults requiring a higher level of care after discharge. 35 This is in comparison to research from California that has found a lower 1-year survival rate after admission for RSV than for influenza (74.2% versus 81.2%, p < 0.001). 36 Each year, 7 in 10 Canadian older adults choose to be vaccinated against influenza, 37 an indication that the majority view the consequences of influenza to be a greater risk than the potential for any adverse events associated with vaccination.…”
Section: Complacency and Rsv Vaccinationcontrasting
confidence: 46%
“…Indeed, taking the estimates for children aged 0-4 years into account; we estimate that 39% (145 604 out of 371 299) of the annual number of RSV-associated hospitalisations in the EU occurred in persons aged 65 years and older. With the changing demographics across Europe where elderly populations are increasing in size and considering the fact that RSV hospitalisation in adults can lead to acute functional decline and reduced quality of life [26], there is a need to get better data and estimates of the true burden of RSV in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, during the RSV‐ARI episode, placebo recipients experienced a decrease of approximately 10 points from baseline in their SF‐12 PF score. Branche et al reported that some older adults with RSV, in particular hospitalized individuals, demonstrate acute functional decline that may become prolonged 8 . The difference in SF‐12 PF LSMean estimates between groups during the RSV‐ARI episode was seven points, suggesting that the impact of RSV on PF was lower in the vaccinated group.…”
Section: Discussionmentioning
confidence: 99%
“…7 Some older adults with RSV infection, especially hospitalized individuals, demonstrate acute functional decline that may become prolonged and can result in higher level of care at discharge and loss of previous independence. 8 The GSK RSV candidate vaccine for older adults (RSVPreF3 OA) is a combination of the RSVPreF3 antigen, a recombinant F protein antigen engineered to preferentially maintain its prefusion form, and GSK's Adjuvant System 01 E (AS01 E ), an adjuvant system that promotes induction/boosting of antibody and cellular responses to overcome age-related decline in immunity. 9 The recombinant RSVPreF3 OA vaccine had 71.7% efficacy (VE) against RSV-ARI and 82.6% VE against RSV-LRTD in adults aged ≥60 years in a phase 3 clinical trial (AReSVi-006/NCT04886596).…”
Section: Introductionmentioning
confidence: 99%